The future of work in the United States: discourses on automation and the platform economy - Rauscher, Natalie (Contributions to Economics, 2021)
Chapter 1. Introduction: Focus, Scope and Structure of the Book -- Chapter 2. The Network Society, the Internet, and the Beginning of the New Economy -- Chapter 3. A New World of Work: The Sharing Economy Platforms -- Chapter 4. Corpus Analysis: Automation, the Future of Work, and the Platform Economy Reflected in Political and Public Discourse -- Chapter 5. Quantitative Analysis: Frequency Analysis -- Chapter 6. Qualitative Analysis: Collocations and Contextual Reading -- Chapter 7. The Discourse around Technological Progress and the Future of Work.